Laparoscopic total extraperitoneal approach versus open lichtenstein repair of primary unilateral uncomplicated inguinal hernia: a prospective randomised controlled trial in Hospital Selayang, selangor - Yen, Fong Voon (2013)
The optimal technique for inguinal hernia repair remains contentious. Laparoscopic surgery has emerged as a new treatment modality for inguinal hernia repair recently and it creates controversy because its benefits are debatable. Endoscopic totally extraperitoneal inguinal hemioplasty (TEP) has been gaining popularity in recent years with plentiful evidence regarding its use for primary inguinal hernia, but there is a paucity of literature concerning its outcome and little data to support the superiority of TEP over open repair. The aims of this study were to determine the suitability and safety of carrying out elective laparoscopic hernia repair compared to open hernia repair for primary uncomplicated unilateral inguinal hernia within a randomized clinical trial. Other specific parameters such as perioperative results and post operation complications between these 2 methods were also included in this study. This was a prospective randomized clinical trial with a total of 86 consecutive patients with primary inguinal hernia Nyhus I to III were randomized to either totally extraperitonal inguinal hemioplasty or open Lichtenstein inguinal hemiopasty between 1 st March 2012 till 1st September 2012 in Hospital Selayang. There were a total of 86 patients enrolled in this study, with 42 patients in the TEP group and 44 patients in open group respectively. However 2 patients from TEP group were converted to transabdominai preperitoneal repair (TAPP) due to breach of peritoneum intraoperatively and they were excluded from the study. Mean operation duration in the open group (62.27 minutes, SD 17.70) was slightly shorter compared to the laparoscopic group (62.50 minutes, SD 14.16) with a mean difference of 0.23 minutes (Ci -7.23, 6.78). Mean length of return to work in the open group (8.91 days, SD 4.64) was significantly longer compared to the laparoscopic group (6.75 days, SD 2.78) with a mean difference of 2.16 days (CI 0.48, 3.84) with p=0.012. There was no statistical significance between 2 groups in concerning to post operation pain scales within 6 hours, 1 day, 1 week, 6 weeks and 6 months. Laparoscopic repair was associated with significantly fewer postoperative complications which were wound infection (p=0.013) and chronic groin pain (p=O.O32). Conclusion: This study proved that TEP conferred significant early postoperative benefits, including faster return to work, a lower wound morbidity rate and reduced postoperative chronic groin pain at 1 week. It showed that TEP was acceptably suitable and safer to be performed compared to open repair for primary uncomplicated unilateral inguinal hernia.